Importance of socio-economic factors in the collection of NTFPs: The case of gum arabic in Kenya - Mujawamariya, Gaudiose; Karimov, A.A. (2014)
Collection of wild non-timber forest products may improve the livelihoods of communities through their direct consumption or marketing. Gum arabic is one of these products by ‘Acacia senegal’ trees that are found in Kenya. It is a source of additional income for rural households. The study explores — household decisions to collect gum arabic in the forest using the two stage Heckman selection model. The data for the analysis come from the 213 randomly sampled collectors from the north-eastern and western regions of Kenya. The findings show that livestock ownership, possession of skills, insecurity and price obtained from the previous season impact on decision making to collect gum arabic. Furthermore, household's age, experience in collecting gum arabic and topography increase the quantities collected while gender negatively impacts amounts of collection. The research concludes by emphasizing that collection of the non-timber forest products including gum arabic would be attractive if the returns from collection justify the risk and cost to go to the forest.